Determination of Meconium Stained Liquor among Fetal Distress Lead Cesarean Mothers - Syeda Tahira Sherazi, Shazia Batool, Amna Noor, Sana Javed, Ayesha Hussain Sial, Muhammad Kashif Munir (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of meconium stained liquor in females undergoing cesarean section due to fetal distress. Study type, setting & duration: This descriptive study was conducted at Unit III, Department of Obstetrics & Gynecology, Ganga Ram Hospital, Lahore during August 2018 to February 2019. Methodology: The study was commenced on 240 females fulfilled selection criteria. After taking informed consent their demographic all females underwent cesarean section. During cesarean section, amniotic fluid was evaluated for meconium staining. All the information was recorded in pre-designed Performa. Data was entered and analyzed in SPSS. Results: Mean age of females was 29.05±6.22years, the mean gestational age was 39.48±1.09 weeks and mean BMI of patients was 26.45±4.70 kg/m2. There were 35 (14.6%) patients of parity 0, 72 (30%) had parity 1, 47 (19.6%) had parity 2, 46 (19.2%) had parity 3 and 40 (16.7%) had parity. The meconium stained liquor was present in 40 (16.7%) patients while absent in 200 (83.3%) patients. Practical implication of this study suggests that meconium stained liquor must be observed closely in females bearing a higher gestational age to avoid meconium aspiration syndrome among neonates. Conclusion: Present study suggests a higher frequency of meconium stained liquor and a higher gestational age is associated with higher frequency of meconium stained liquor while no association of age, parity strata and BMI were found. Key words: Cesarean section, pregnancy, trimester, parity, Meconium Aspiration Syndrome, Meconium Stained Liquor.